A framework for remission in SLE: consensus findings from a large international task force on definitions of remission in SLE (DORIS). Issue 3 (24th November 2016) - van Vollenhoven, Ronald; Voskuyl, Alexandre; Bertsias, George; Aranow, Cynthia; Aringer, Martin; Arnaud, Laurent; Askanase, Anca; Balážová, Petra; Bonfa, Eloisa; Bootsma, Hendrika; Boumpas, Dimitrios; Bruce, Ian; et al.
Abstract : Objectives: Treat-to-target recommendations have identified 'remission' as a target in systemic lupus erythematosus (SLE), but recognise that there is no universally accepted definition for this. Therefore, we initiated a process to achieve consensus on potential definitions for remission in SLE. Methods: An international task force of 60 specialists and patient representatives participated in preparatory exercises, a face-to-face meeting and follow-up electronic voting. The level for agreement was set at 90%. Results: The task force agreed on eight key statements regarding remission in SLE and three principles to guide the further development of remission definitions: 1. Definitions of remission will be worded as follows: remission in SLE is a durable state characterised by …………………. (reference to symptoms, signs, routine labs). 2. For defining remission, a validated index must be used, for example, clinical systemic lupus erythematosus disease activity index (SLEDAI)=0, British Isles lupus assessment group (BILAG) 2004 D/E only, clinical European consensus lupus outcome measure (ECLAM)=0; with routine laboratory assessments included, and supplemented with physician's global assessment. 3. Distinction is made between remission off and on therapy: remission off therapy requires the patient to be on no other treatment for SLE than maintenance antimalarials; and remission on therapy allows patients to be on stable maintenance antimalarials, low-dose corticosteroids (prednisone ≤5 mg/day), maintenance immunosuppressives and/or maintenance biologics. The task force also agreed that the most appropriate outcomes (dependent variables) for testing the prognostic value (construct validity) of potential remission definitions are: death, damage, flares and measures of health-related quality of life. Conclusions: The work of this international task force provides a framework for testing different definitions of remission against long-term outcomes.